2010
DOI: 10.1111/j.1939-1676.2009.0413.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Evaluation of Gallbladder Bile of Healthy Dogs and Dogs with Iatrogenic Hypercortisolism: A Pilot Study

Abstract: Background: In people, hypercortisolism (HC) has been associated with acalculous cholecystitis and biliary dyskinesia, which may potentiate ascending biliary infections. In dogs, an association between HC and gallbladder disease recently has been documented, although the role of bacteria remains controversial. Furthermore, there is no information on the gallbladder bile microbial flora in healthy dogs.Objectives: To investigate the microbial flora in gallbladder bile in healthy dogs, the relationship between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
3
29
3
Order By: Relevance
“…Complications directly attributable to cholecystocentesis were low in this study, and comparable to previous reports,5, 16, 17 but nonetheless 2 dogs (<2% of all cases with available follow‐up information) suffered from iatrogenic bile peritonitis. However, necropsy findings suggested that bile peritonitis was not the predominant disease process in either case.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Complications directly attributable to cholecystocentesis were low in this study, and comparable to previous reports,5, 16, 17 but nonetheless 2 dogs (<2% of all cases with available follow‐up information) suffered from iatrogenic bile peritonitis. However, necropsy findings suggested that bile peritonitis was not the predominant disease process in either case.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of dogs with bactibilia in our study lacked cytological evidence of concurrent inflammation, raising the possibility of transient colonization rather than true infection. Transient, self‐limiting bactibilia can occur in clinically healthy dogs,5 but lack of concurrent inflammation in the bile or gallbladder wall despite bactibilia also occurs in clinically sick dogs 2, 7, 9. Although most of the animals had clinical signs of hepatobiliary disease, these could not be clearly attributed to gallbladder disease in cases from Group 2, as comorbidities were present in most cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although immunosuppression from corticosteroids alone cannot be ruled out, it appears less likely as hepatobiliary infection has not been demonstrated in beagles following chronic iatrogenic hypercortisolism (Kook et al . ). Translocation of enteric microorganisms is plausible given that severe chronic cobalamin deficiency may impact on the rapidly proliferating intestinal epithelium (Arvanitakis ).…”
Section: Discussionmentioning
confidence: 97%
“…915F&G). Although bile is generally sterile, studies indicate that clinically healthy dogs may occasionally yield positive bacterial cultures without clinical significance (Kook et al, 2010). Cholecystitis is an infrequent disease of dogs but more commonly in cats, which present with vomiting and anorexia and elevated concentrations of cholestatic enzymes [ALP and gammagluta myltransferase (GGT)].…”
Section: Neutrophilic Lymphocytic and Mixed Cell Inflammationmentioning
confidence: 99%